Effects of voluntary running exercise on skeletal muscle properties in nonobese rats with type 2 diabetes - Nakamoto, I; Ishihara, A (Physiological research, 2020)
The skeletal muscles of animals and humans with type 2 diabetes have decreased oxidative capacity. Aerobic exercise can improve muscle oxidative capacity, but no data are available on the amount of exercise required. We investigated the effects of voluntary running exercise and running distance on the skeletal muscle properties of nonobese rats with type 2 diabetes. Six-week-old male diabetic Goto-Kakizaki rats were divided into nonexercised (GK) and exercised (GK-Ex) groups. The rats in the GK-Ex group were permitted voluntary running exercise on wheels for 6 weeks. Age-matched male Wistar rats (WR) were used as nondiabetic controls. Fasting blood glucose and HbA1c levels were higher in the GK and GK-Ex groups than in the WR group and lower in the GK-Ex group than in the GK group. Succinate dehydrogenase (SDH) activity and peroxisome proliferator-activated receptor gamma coactivator-1alpha (Pgc-1alpha) mRNA levels in the soleus and plantaris muscles were higher in the WR and GK-Ex groups than in the GK group. HbA1c and total cholesterol levels were negatively correlated with running distance and SDH activity and Pgc-1alpha mRNA levels in the soleus muscle were positively correlated with running distance. The onset and progression of diabetes in nonobese diabetic rats were effectively inhibited by running longer distances.
Keywords: Diabetes Mellitus, Type 2; Rats; Physical Conditioning, Animal; kosterní svaly; kondiční příprava zvířat; Animals; krysa rodu Rattus; Succinate Dehydrogenase; mužské pohlaví; Male; diabetes mellitus 2. typu; PPARGC1A; zvířata; krevní glukóza; Blood Glucose; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; Muscle, Skeletal; sukcinátdehydrogenasa